2021
DOI: 10.3389/fimmu.2020.601639
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Proteoforms of the Transmembrane Chemokines CXCL16 and CX3CL1, Their Receptors, and Their Processing Metalloproteinases ADAM10 and ADAM17 in Proliferative Diabetic Retinopathy

Abstract: The transmembrane chemokine pathways CXCL16/CXCR6 and CX3CL1/CX3CR1 are strongly implicated in inflammation and angiogenesis. We investigated the involvement of these chemokine pathways and their processing metalloproteinases ADAM10 and ADAM17 in the pathophysiology of proliferative diabetic retinopathy (PDR). Vitreous samples from 32 PDR and 24 non-diabetic patients, epiretinal membranes from 18 patients with PDR, rat retinas, human retinal Müller glial cells and human retinal microvascular endothelial cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(50 citation statements)
references
References 81 publications
(158 reference statements)
1
44
0
5
Order By: Relevance
“…Angiogenesis and inflammation are the key feature of PDR and also thought to be critical mechanisms for PDR initiation and progression ( 3 , 15 ). In this study, we showed higher vitreous levels of angiogenesis and inflammation mediators including syndecan-1, PIGF, ANGPTL-4, VEGF and IL-8 in eyes with PDR.…”
Section: Discussionmentioning
confidence: 99%
“…Angiogenesis and inflammation are the key feature of PDR and also thought to be critical mechanisms for PDR initiation and progression ( 3 , 15 ). In this study, we showed higher vitreous levels of angiogenesis and inflammation mediators including syndecan-1, PIGF, ANGPTL-4, VEGF and IL-8 in eyes with PDR.…”
Section: Discussionmentioning
confidence: 99%
“…12 Our hypothesis-driven approach identified PDGF as a major inducer of neurite outgrowth, but this does not exclude that other growth factors and cytokines may also play an important role in neurite outgrowth in PDR. For example, two recent studies showed the involvement of the chemokine axis CXCL16/CXCR6 and the metalloproteinases ADAM10 and ADAM17 30 and the involvement of CD146 31 in vitreous of PDR patients, FVMs and in Müller cell activation.…”
Section: Discussionmentioning
confidence: 99%
“…CX3CL1 is a membrane-bound chemokine, which functions as an adhesion molecule for leukocytes, but can also be proteolytically cleaved, resulting in a soluble form with chemotactic function (97, 98). Several studies already demonstrated the implication of CX3CL1 in DR pathogenesis as the vitreous of PDR patients contains elevated levels of CX3CL1 (99) Furthermore, circulating CD11b+ leukocytes that are involved in leukostasis in DR express higher levels of CX3CR1 in diabetic mice compared to controls (100). Thus, membrane-bound CX3CL1 on the surface of Müller cells might be involved in leukostasis in DR.…”
Section: Discussionmentioning
confidence: 99%